High rate and temperature-dependent tensile characterisation with modelling for gap-bridged remote laser welded (RLW) joint using automotive AA5182 alloy. (October 2020) - Das, Abhishek; Beaumont, Richard; Butterworth, Ian; Masters, Iain; Williams, David
Highlights: Part-to-part 'gap-bridged' Remote Laser Welded (RLW) joint behaviours are quantified from moderate (0.1 m/s) to high speed rate (10 m/s) at room temperature. The effects of depressed (-50 °C) to elevated temperatures (up to 300 °C) on the RLW fillet edge welds were evaluated. The fracture strain across weld area was in the range from 0.140 to 0.194 for all the part-to-part gap and test speed conditions. Modelling and simulation performed to identify the joint behaviours beforehand. Lap shear strength was compared between RLW, self-piercing riveting and resistance spot welding. Abstract: This paper investigates the high rate tensile behaviour of fillet edge joints produced by 'gap-bridged' remote laser welding (RLW) using aluminium alloy AA5182. The RLW 'gap-bridged' test specimens were produced considering three levels of the part-to-part gap; 0.0, 0.2, and 0.4 mm. Lap shear tests were performed to evaluate the high rate sensitivity in the test speed range from moderate (0.1 m/s) to high-speed rate (10 m/s) at room temperature (~23 °C). This equates to a strain rate range from moderate (~ 10 s −1 ) to near 1000 s −1 . Strain rate dependency was found to be low, however, an increase in tensile extension to failure was observed with increasing strain rate. Additionally, the effects of depressed (−50 °C) to elevated temperatures (up to 300  °C) on the joint tensile performance were evaluated. Fracture strain was computed at room temperature using the digital image correlation (DIC) method and the fracture strain across the weld area was in the range from 0.140 to 0.194 for all the gap and speed conditions. This paper compares the RLW experimental test results with finite element modelling for industrial use. To evaluate joint performance, the lap shear strength of RLW samples was also compared with self-piercing riveting and resistance spot welding.